98.6k views
3 votes
(8 - 11) x 1-11 + 7) = ?
A. -54
B. -12
C. 12
D. 54
E. 76

(8 - 11) x 1-11 + 7) = ? A. -54 B. -12 C. 12 D. 54 E. 76-example-1

2 Answers

3 votes

Answer:

B. -12

Explanation:

(8-11)*l -11 +7 l =

Solve inside the parentheses

8-11 = -3

Solve inside the absolute value signs

-11+7 = -4

Take the absolute value of - 4

l-4l = 4

Multiply -3 and 4

-3*4 = -12

So the answer is B. -12

User BachT
by
5.1k points
3 votes

Answer:

its B.

Explanation:

hope this helps ~( ̄▽ ̄)~*

User SparcU
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.